Kajian Sosiolinguistik pada “Nama Orang” di Jawa Timur - Mochamad Faizal Mohtarom; Ika Nurhayani; Esti Junining (Kode : Jurnal Bahasa, 2023)
This study aims to analyze the changes in the meaning of "person's name" in East Java Society. The significance of people's "names" holds importance due to differences in naming practices and their meanings across generations, specifically the X, Y, Z, and Alpha generations. A sociolinguistic perspective is employed in this study, utilizing a descriptive qualitative research method. Primary data is collected through interviews and observations, while secondary data is obtained through relevant document searches. The findings reveal that the naming patterns differ for each generation, including X, Y, Z, and Alpha, depending on the parents' expectations for their child's name. These expectations are influenced by external factors such as religion, date and month of birth, and socio-cultural aspects, as well as internal factors such as parents' preferences for specific languages or characters from certain stories. In conclusion, Javanese names and their meanings have undergone shifts across generations, both in terms of the number of words and language choices. The X generation tends to have fewer words compared to the Y, Z, and Alpha generations. Similarly, the Y generation exhibits relatively fewer and shorter names compared to the Z and Alpha generations. Regarding language, the most recent generations, Z and Alpha (1997-present), incorporate a greater variety of foreign languages into their names compared to the previous generations (X and Y) of Javanese names. Kata Kunci: Pergeseran Nama, Makna, Sosiolingusitik